2013
DOI: 10.1080/00455091.2013.816176
|View full text |Cite
|
Sign up to set email alerts
|

On preferring God's non-existence

Abstract: For many centuries, philosophers have debated this question: ‘Does God exist?’ Surprisingly, they have paid rather less attention to this distinct – but also very important – question: ‘Would God's existence be a good thing?’ The latter is an axiological question about the difference in value that God's existence would make (or does make) in the actual world. Perhaps the most natural position to take, whether or not one believes in God, is to hold that it would be a very good thing if such a being were to exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…Both of these positions can be subdivided to account for the value impact of God's existence on a particular person (personal scope), or all persons more generally (impersonal scope). Further subdivisions can be made to account for things that would be better in some particular respect (narrow scope), or overall (wide scope) (Kraay & Dragos ) . It has been noted that these categories ‘cut across each other, and generate four varieties of anti‐theism [and also of pro‐theism]’ (Kraay & Dragos, , p. 159):
Wide Impersonal Anti‐Theism: It would be far worse overall if God exists than if God does not.Wide Impersonal Pro‐Theism: It would be far better overall if God exists than if God does not.Wide Personal Anti‐Theism: It would be far worse overall for me if God exists than if God does not.Wide Personal Pro‐Theism: It would be far better overall for me if God exists than if God does not.Narrow Impersonal Anti‐Theism: It would be far worse in certain respects if God exists than if God does not.Narrow Impersonal Pro‐Theism: It would be far better in certain respects if God exists than if God does not.Narrow Personal Anti‐Theism: It would be far worse in certain respects, for me , if God exists than if God does not.Narrow Personal Pro‐Theism: It would be far better in certain respects, for me , if God exists than if God does not
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these positions can be subdivided to account for the value impact of God's existence on a particular person (personal scope), or all persons more generally (impersonal scope). Further subdivisions can be made to account for things that would be better in some particular respect (narrow scope), or overall (wide scope) (Kraay & Dragos ) . It has been noted that these categories ‘cut across each other, and generate four varieties of anti‐theism [and also of pro‐theism]’ (Kraay & Dragos, , p. 159):
Wide Impersonal Anti‐Theism: It would be far worse overall if God exists than if God does not.Wide Impersonal Pro‐Theism: It would be far better overall if God exists than if God does not.Wide Personal Anti‐Theism: It would be far worse overall for me if God exists than if God does not.Wide Personal Pro‐Theism: It would be far better overall for me if God exists than if God does not.Narrow Impersonal Anti‐Theism: It would be far worse in certain respects if God exists than if God does not.Narrow Impersonal Pro‐Theism: It would be far better in certain respects if God exists than if God does not.Narrow Personal Anti‐Theism: It would be far worse in certain respects, for me , if God exists than if God does not.Narrow Personal Pro‐Theism: It would be far better in certain respects, for me , if God exists than if God does not
…”
Section: Introductionmentioning
confidence: 99%
“… Two other possible stances are agnosticism and indifference but I will not discuss these here (Kraay & Dragos, , p. 159).…”
mentioning
confidence: 99%
“…As Kraay and Dragos (2013) point out, it is a logical truth that God cannot allow any gratuitous evil. An all-powerful, all-knowing, all-good creator would not and could not create a world with senseless or avoidable suffering.…”
mentioning
confidence: 99%
“…It is a world where we are the subordinates of a moral superior, a superior that deserves our allegiance and worship…The idea is that God's existence is logically incompatible with the full realization of certain values. Thus a world in which God exists is a world where we would not be the moral equals of all other rational beings-equal members of a kingdom of ends 1 For work on this issue, see Kahane (2011); Kahane (2012); Kraay and Dragos (2013);and Mawson (2012). 2 Russell and Camus are two Non-Theists who suggested that the world might be better at least in certain respects if God existed.…”
mentioning
confidence: 99%
See 1 more Smart Citation